Business models for supporting energy renovation in residential buildings. The case of the on-bill programs - Vincenzo Bianco; Paolo Michele Sonvilla; Pablo Gonzalez Reed; Adriana Villoslada Prado (Energy Reports, 2022)
On-bill schemes are innovative financial frameworks for supporting investments in energy efficiency with a particular focus on residential buildings. These schemes are interesting since they allow to attract private capital in the energy efficiency market, and they also see the involvement of energy utilities which can be regarded as market aggregators. Despite the conceptual simplicity of these mechanisms, namely the utility provides upfront capital for the investment which is repaid by final users on the bill in a number of years, solid and innovative business models are necessary to support their development and implementation. To this aim the present paper employs the Value Flow Model to develop four business models to implement on-bill schemes. In particular, standard on-bill financing and on-bill repayment business models are developed in detail. In addition, more complicated and innovative business models, namely on-bill repayment via a Special Purpose Vehicle and on-bill repayment with a Master Servicer, are also developed for more complex schemes. These four fundamental business models can be used and adapted according to market context of operation. Finally, the possible involvement of Distribution System Operators as service providers or facilitators for on-bill schemes is also outlined.